Training application anates used the Contextual Learning Teaching (CTL) integrated social class on teachers are economic subjects Muhammadiyah 6 the Junior High School - Stevani Stevani; Vivina Eprillison; Meri Rahmania; Yuli Diniah Zilbakri (Universitas PGRI Sumatera Barat, 2021)
One of application used to analyze about the anates.Anates this is a software application program of computer that purpose to analyze about.The use of software is very anates required by teachers in evaluate study results also work to students and scholars education evaluation.But teachers still difficulty in using the software program of analysis about anates because teachers do not yet know and understand how to operate the software anates. Doing these activities is to share knowledge pengetahun for teachers to analyse matter in application of as anates use approach kontekstual belajar mengajar ctl ( ips ) for the teacher integrated economic subjects the junior high school muhammadiyah 6 Padang.